Synthesis of 2-(Benzylthio)-4-(trifluoromethyl)thiazole-5-carboxylates Using S-Benzylisothiouronium Halides as Thiol Equivalents - Hickey, Shane M.; White, Jonathan M.; Pfeffer, Frederick M.; Ashton, Trent D. (Synlett, 2015)
S-Benzylisothiouronium halides are used as shelf-stable, odorless thiol equivalents. The method developed is used to access 2-(benzylthio)-4-(trifluoromethyl)thiazole carboxyl building blocks. Using the latent trifluoromethyl substituent the reactions could be monitored using 19F NMR spectroscopy.
Keywords: thioether; isothiouronium halide; 19F NMR spectroscopy; nucleophilic aromatic substitution; thiazole